Interactive Multimedia as a Catalyst for Improving Students’ Mathematical Problem-Solving Ability - Nur Wasi'ah; Adi Nur Cahyono (FKIP UNIVERSITAS PAKUAN, 2025)
Students in Indonesia often have difficulties in mathematics problem-solving, mainly due to the absence of engaging media in traditional teaching techniques. This study aimed to examine the effect of interactive learning multimedia on students' mathematical problem-solving skills. We performed a Systematic Literature Review (SLR), examining 20 papers, of which 15 were selected from accredited national journals (Sinta 1-5) sourced from Scopus and Google Scholar, with a specific emphasis on